Kepuasan dan Motivasi Kerja Karyawan Service Advisor di Auto2000 Plaju - Duta Permana; Mukran Roni (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze job satisfaction and work motivation of Service Advisor employees at Toyota Auto2000 Plaju and their impact on service performance. The background of the research is based on the important role of Service Advisors as the frontline of customer service who face high work pressure, service targets, and various customer characters. The research method used a qualitative approach with data collection techniques through direct observation, in-depth interviews with three Service Advisors, and documentation during the internship. The results showed that the level of job satisfaction of Service Advisors was relatively good, characterized by a comfortable work environment, harmonious working relationships with colleagues and superiors, and a compensation and reward system that matches job responsibilities. Employee work motivation was also in the high category, driven by internal factors such as economic needs, career development aspirations, and pride in working at a large company, as well as external factors such as support from supervisors and coworkers. Service Advisor performance was reflected in their ability to provide professional service, clear communication with customers, and good coordination with technicians. The study also identified that the main challenge faced was the surge in the number of customers at certain times which increased the workload. This study concludes that job satisfaction and work motivation have a positive contribution to improving Service Advisor performance. Therefore, the company is advised to maintain a conducive work environment, improve reward programs, and provide competency development opportunities to support optimal service and customer satisfaction.